Zooplankton sampling during the 55th Japanese Antarctic Research Expedition in austral summer 2013–2014 - TAKAHASHI, Kunio T.; IIDA, Takahiro; OJIMA, Motoha; ODATE, Tsuneo (2015)
Fig. 1, 2 | http://polaris.nipr.ac.jp/~parc/pub/v006/nipr_parc_175_0014.doc Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_175_0011.doc Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v002/nipr_parc_175_0012.doc Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v003/nipr_parc_175_0013.doc Table 4 | http://polaris.nipr.ac.jp/~parc/pub/v004/nipr_parc_165_0010.doc Table 5 | http://polaris.nipr.ac.jp/~parc/pub/v005/nipr_parc_165_0011.doc departmental bulletin paper